Decline in resting heart rate, its association with other variables, and its role in cardiovascular disease The Tromsø Study - Sharashova, Ekaterina (UiT The Arctic University of Norway, 2017)
The papers of this thesis are not available in Munin. Paper I: Sharashova, E., Wilsgaard, T., Brenn, T.: “Resting heart rate on the decline: the Tromsø Study 1986-2007”. Available in Int J Epidemiol 2015, 44(3):1007-1017. Paper II: Sharashova, E., Wilsgaard, T., Mathiesen, E. B., Løchen, M. L., Njølstad, I., Brenn, T.: “Resting heart rate predicts incident myocardial infarction, atrial fibrillation, ischaemic stroke and death in the general population: the Tromsø Study”. Available in J Epidemiol Community Health 2016, 70(9):902-909. Paper III: Sharashova, E., Wilsgaard, T., Løchen, M. L., Mathiesen, E. B., Njølstad, I., Brenn, T.: “Resting heart rate trajectories and myocardial infarction, atrial fibrillation, ischemic stroke and death in the general population: the Tromsø Study”. (Manuscript). Background: Resting heart rate (RHR) is an easily measured cardiovascular parameter that is considered an independent predictor of cardiovascular disease (CVD) and mortality in the general population. However, results on the association between RHR and these outcomes are inconsistent, and studies on longitudinal trends in RHR and the role of long-term changes in RHR in CVD and mortality are scarce. Objective: To investigate secular trends in RHR in the general population of Tromsø, Northern Norway over the last decades, and to explore the role of RHR and long-term changes in RHR in CVD and mortality. Methods: Participants from four surveys of the Tromsø Study conducted between 1986 and 2008 were included in these analyses (n=34 751). RHR in these participants was measured with an automated Dinamap device and resultant data were linked to validated information on incident myocardial infarction, atrial fibrillation, ischemic stroke, cardiovascular death and total death. Statistical methods included mixed models analysis, fractional polynomials, and trajectory analysis. Main results: Over 22 years of observation, the mean age-adjusted RHR declined from 73.4 to 64.7 beats per minute in men, and from 78.3 to 66.4 beats per ...